2016
DOI: 10.1038/srep21005
|View full text |Cite|
|
Sign up to set email alerts
|

Wharton’s jelly-derived mesenchymal stem cells combined with praziquantel as a potential therapy for Schistosoma mansoni-induced liver fibrosis

Abstract: Liver fibrosis is one of the most serious consequences of S. mansoni infection. The aim of the present study was to investigate the potential anti-fibrotic effect of human Wharton’s jelly-derived mesenchymal stem cells (WJMSCs) combined with praziquantel (PZQ) in S. mansoni-infected mice. S. mansoni-infected mice received early (8th week post infection) and late (16th week post infection) treatment with WJMSCs, alone and combined with oral PZQ. At the 10th month post infection, livers were collected for subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 57 publications
(62 reference statements)
0
28
0
Order By: Relevance
“…Schistosoma infection is a widespread parasitic infectious disease and the liver injury induced by parasite egg is still a challenge for clinical treatment [1]. MSC transplantation is thought to be quite effective [6,7,24,25]; however, this approach has been hindered by the concerns that MSCs might trigger pulmonary embolism in some clinical settings [26]. In the present study, we found that like hUCMSCs, EVs derived from hUCMSCs have also the capacity to ameliorate S. japonicum-induced liver damage and increased survival of schistosome-infected mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Schistosoma infection is a widespread parasitic infectious disease and the liver injury induced by parasite egg is still a challenge for clinical treatment [1]. MSC transplantation is thought to be quite effective [6,7,24,25]; however, this approach has been hindered by the concerns that MSCs might trigger pulmonary embolism in some clinical settings [26]. In the present study, we found that like hUCMSCs, EVs derived from hUCMSCs have also the capacity to ameliorate S. japonicum-induced liver damage and increased survival of schistosome-infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…i The number of schistosome eggs in the liver was measured after the liver tissue was digested by 4% KOH. Mean values ± SD for three independent experiments are shown, *P < 0.05; **P < 0.01; ***P < 0.001, compared with the PBS group damage in mice infected with S. mansoni [7], it still remains unclear the effect of hUCMSCs on the outcome of schistosomiasis, especially schistosomiasis japonica, a parasitic disease with more egg deposition in host liver and more severe liver damage. In this study, we are the first to report that hUCMSC treatment increases the survival of S. japonicum-infected mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pretreatment of fibrotic liver with IL‐6 significantly improves the survival rate of MSCs, thus providing more effective antifibrotic effects by improving glycogen storage, moreover, the pretreatment also demonstrated a significant reduction in lactate dehydrogenase release and apoptosis in hepatocytes via up‐regulation of Bcl‐xl and down‐regulation of Bax, caspase‐3, NFκB and TNF‐α . In Schistosoma mansoni ‐induced liver fibrosis, oral praziquantel treatment further enhanced the beneficial effects of MSC transplantation on regression of liver fibrosis as demonstrated by down‐regulation of α ‐SMA, COL1A1 and IL‐13 in liver tissue and other parameters such as morphometric, histopathological and gelatin zymographic results …”
Section: Preconditioning Of Recipientsmentioning
confidence: 97%
“…In the current study, liver infection was induced by subcutaneous infection of immuno-competent Balb/C mice with 90 cercariae of S. mansoni . This technique was also performed by other authors as Gryseels et al (2006) ; Elkhafif et al (2010) ; Hammam et al, (2016) , who reported that inflammatory granulomas were formed inside livers of infected mice. Gryseels et al (2006) described the acute liver granuloma on infected mouse (6-10weeks) post infection that appeared with different inflammatory cells, mainly eosinophils, lymphocytes, and macrophages.…”
Section: Discussionmentioning
confidence: 91%